If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = -2x + -16 Reorder the terms: 3(-2 + x) = -2x + -16 (-2 * 3 + x * 3) = -2x + -16 (-6 + 3x) = -2x + -16 Reorder the terms: -6 + 3x = -16 + -2x Solving -6 + 3x = -16 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 3x + 2x = -16 + -2x + 2x Combine like terms: 3x + 2x = 5x -6 + 5x = -16 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 5x = -16 + 0 -6 + 5x = -16 Add '6' to each side of the equation. -6 + 6 + 5x = -16 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = -16 + 6 5x = -16 + 6 Combine like terms: -16 + 6 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| m^3n+9m^2n= | | 4(2x+3u)-3(x-y)= | | 9x^3+30x= | | 45x^2-20x= | | 2*N=12 | | 2XN=12 | | 29-(2c+3)=2(c+3)+c | | p^2+2pq+q^2-2p-2q-15=0 | | 3(m+4)=39 | | 12+36x+27x^2=0 | | x-2x-25=0 | | t^4-7t^2-18=0 | | X=8+9Y-5*2 | | x=x+6 | | 60[100s]= | | 10x^2+21x-27=0 | | 28+x=24 | | 12d-6+4d= | | N+17=22 | | (y-2)-(Y+6)=4Y | | 19-A=3 | | 21=7S | | -380+x+x^2=0 | | 99-M=3 | | 7x-4-5x+2=10x+6-7x-4 | | a^2-18ab-40b^2= | | 2x^2-3x=35 | | 3(t-1)=qt | | -15=5b+12-2b | | 8a+20b=100 | | 99-M=72 | | a^2+17ab+72b^2= |